O exercício físico agudo modifica o padrão de sono, as funções cognitivas e o estado de humor em condição de hipóxia? - Lemos, Valdir de Aquino [UNIFESP] (2016)
Introduction: Although there is controversy, hypoxia can change the mood, sleep pattern and various cognitive functions, including memory, attention, executive functions, decision making, reaction time and so on. On the other hand, when the exercise performed in normoxia condition can improve all of these functions. Objective: To evaluate the influence of two exercise sessions at 50% of VO2peak. held in hypoxic condition (equivalent to 4,500 m for 29 hours) on sleep, mood and cognitive functions in healthy young people. Method: The sample consisted of 40 healthy volunteers of males aged between 20 and 30 years, divided into 4 groups. Normoxia (n = 10) (GN), hypoxia (n = 10) (GH), exercise in normoxic (n = 10) (GEN) and exercise in hypoxia (n = 8) (GEH). The experimental protocol lasted 2 days and 2 consecutive nights with 28 hours of hypoxia exposure. Memory was assessed, attention, decision making, reaction time (RT), executive functions and intellectual potential, besides the mood. These assessments were performed twice, first in normoxic and the second after 28 hours in hypoxia. The sleep was evaluated by polysomnography in two stages: the first in normoxia and hypoxia in the second. Results: In hypoxia after exercise there was improvement in sleep efficiency, stage N3 and REM and reduced wake after sleep onset (p <0.05). The voltage scores, angry and depressed mood, vigor and cognitive functions improve after exercise in hypoxia (p <0.05). Conclusions: We conclude that hypoxia worsens sleep, and mood and cognitvas functions. The acute physical exercise at 50% of VO2peak., Hypoxia, improves sleep efficiency reversing the aspects that had been damaged in hypoxic condition and possibly contributing to improved mood and reaction time.